NS1 ANTIGEN DETECTION BY ELISA IN EARLY LABORATORY DIAGNOSIS OF DENGUE INFECTION - T, Deshkar Smita; P, Tore Rajani; S, Raut Sharmila; K, Khadse Ravindra (International Journal of Clinical and Biomedical Research, 2018)
Introduction: Dengue is a major public health problem in tropical and sub-tropical regions of the world and it is known for serious life threatening complications. Detection of IgM antibodies forms the mainstay for diagnosis of dengue infection. However, IgM antibodies develop after 4-5 days of infection and there is an urgent need for an alternative diagnostic tools that can detect dengue infection earlier. Aim and Objectives: To evaluate the efficacy of NS1 antigen ELISA for early diagnosis of dengue virus infection in a tertiary care hospital Methods- A total of 2106 serum samples from patients with suspected dengue infection were tested for dengue NS1 antigen and IgM antibody detection by ELISA. Results: 765 (36.32%) were positive for dengue NS1 antigen and 857 (40.69%) were positive for dengue IgM antibody. NS1 antigen was detectable in patient sera from day 1 onwards however; dengue IgM antibody was detected from day 3 onwards. Out of 765 NS1 antigen positive samples, 562 (73.46%) were positive in acute phase of illness and 203 (26.54%) were positive in convalescent phase of illness. Out of 857 MAC ELISA positive samples, 312 (36.41%) were from acute phase of illness and 545 (63.59%) were from early convalescent phase of illness. Combination of two tests resulted in increase in the positivity rate to 52.66% as against to independent positivity rate of 36.32% of NS1 ELISA and 40.69% of MAC ELISA. Conclusion: Combined use of NS1 antigen assay with MAC ELISA test could significantly improve diagnostic sensitivity of dengue infection